AUDITING FAIR VALUE ESTIMATES IN LIGHT OF THE EFFECTIVENESS OF PROFESSIONAL SKEPTICISM AND THE CHALLENGES FACING THE EXTERNAL AUDITOR. AN ANALYTICAL STUDY OF IRAQI AUDITING FIRMS STUDY OF IRAQI AUDITING OFFICES AND COMPANIES (World Bulletin of Management and Law, 2022)
This research aims to identify the most important challenges facing auditors when measuring fair value and the importance of practicing professional skepticism for the auditor and to indicate the level of auditors' application of the requirements of auditing fair value estimates when auditing the financial statements of private commercial banks, as the auditors' practices in the Iraqi environment lack to adequate perception and guidance regarding fair value estimates in a way that enables them to exercise professional skepticism more effectively. Therefore, the discounted cash flow method was adopted in re-evaluating the investment portfolio for the shares of a number of private commercial banks in the Iraqi environment .
Keywords: fair value; challenges; professional skepticism